Intervento psichiatrico, libertà personale e istituzione carceraria Intervista a Mauro Palma - Alessandra Carlotto (Il sogno della farfalla, 2022)
This article reports an interview to the President of the Italian National Guarantor for rights of people who have lost personal freedom. The aim of this interview is to analyses the current major difficulties of Italian penitentiary institutions in taking care of detainee’s mental health. It is highlighted how legislative shortcomings relate to a culture that disregards both mental and physical health. In order to guarantee the detainees mental health, the president proposes new approaches which take into account both a psychotherapeutic and pharmacological treatment within a multidisciplinary interventional framework.